LITERATURE REVIEW OF PHYTOCHEMICAL PROPERTIES OF FIG (Ficus Carica L) IN SURAH AT-TIN VERSE 1 - Zulkarnain, Zulkarnain; Suprapto, Suprapto; Maigoda, Tony Cortis (Lantanida Journal, 2023)
Allah provides information about the fig plant in Surah At-Tin verse 1. The fig plant is a special plant that is specifically mentioned in the Quran and is widely used for human health such as preventing hypertension, maintaining heart health, and treating diabetes. The fig plant is a plant that has many chemically active compounds that are useful in medicine. This study aims to determine the content of the surah At-Tin verse 1 and identify the features of the fig plant from the perspective of plant phytochemicals. The results showed that Allah swore by the name of the fig plant in Surah At-Tin verse 1. This indicates that there are many blessings on the fig plant for human life. Phytochemical test results showed that the fig plant has chemical compounds that are beneficial to human health such as flavonoids, alkaloids, phenolics, terpenoids, and saponins. These compounds act as anti-oxidants, function in the detoxification of toxins, prevent cancer, regulate the stability of the body's metabolism, and scavenge radicals that enter the body. The fig plant has a high economic value. The cultivation of fig plants is a good economic commodity for the welfare of society. Figs can be processed into products that sell well in the market.